Federal Income Taxation of Corporations and Shareholders (Book). - Griffin, Charles H.; Sommerfeld, Ray M. (The Accounting Review, 1967)
Reviews the book "Federal Income Taxation of Corporations and Shareholders," by Boris Bittker and James Eustice.